2022
DOI: 10.1111/mec.16677
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding and applied ecology with hyperdiverse organisms: Recommendations for biological control research

Abstract: Metabarcoding is revolutionizing fundamental research in ecology by enabling large‐scale detection of species and producing data that are rich with community context. However, the benefits of metabarcoding have yet to be fully realized in fields of applied ecology, especially those such as classical biological control (CBC) research that involve hyperdiverse taxa. Here, we discuss some of the opportunities that metabarcoding provides CBC and solutions to the main methodological challenges that have limited the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 131 publications
(207 reference statements)
0
9
0
Order By: Relevance
“…While the available diet is impacted for both trophic levels, the negative effects of urbanisation are stronger for predators than herbivores, likely due to their increased requirement for larger, unfragmented habitat. The approach can also be used to address applied questions of biological control interactions as reviewed in Lue et al (2022) who showed that it can allow not only identification of biological control interactions but also evidence of hyperparasitism or multiparasitism, which can disrupt biological control by introduced agents.…”
Section: Interaction Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…While the available diet is impacted for both trophic levels, the negative effects of urbanisation are stronger for predators than herbivores, likely due to their increased requirement for larger, unfragmented habitat. The approach can also be used to address applied questions of biological control interactions as reviewed in Lue et al (2022) who showed that it can allow not only identification of biological control interactions but also evidence of hyperparasitism or multiparasitism, which can disrupt biological control by introduced agents.…”
Section: Interaction Networkmentioning
confidence: 99%
“…The importance of a reference collection is highlighted by Lue et al. (2022) who describe the importance of a vetted and curated reference library for biological control studies. Likewise, Lu et al.…”
Section: Invasive Species/homogenizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, rather than diminishing any role of natural history museums in such approaches, the vast data that have been generated through molecular profiling approaches have increasingly highlighted the fundamental importance of barcodes from reliably identified species and populations (Valdivia-Carrillo, Rocha-Olivares, Reyes-Bonilla, Dominguez-Contreras, & Munguia-Vega, 2021). The importance of a reference collection is highlighted by Lue et al (2022) which describes the importance of a vetted and curated reference library for biological control studies. Likewise, Lu et al (2022) emphasize the limitations of inference without a reference database, and introduce a fungal rRNA operon database (FRODO) with 1116 linked to taxonomically identified species.…”
Section: Recurring Themesmentioning
confidence: 99%